2012
DOI: 10.1590/s0100-69162012000100009
|View full text |Cite
|
Sign up to set email alerts
|

Test of a microlysimeter for measurement of soil evaporation

Abstract: Quantifying soil evaporation is required on studies of soil water balance and applications aiming to improve water use efficiency by crops. The performance of a microlysimeter (ML) to measure soil evaporation under irrigation and non-irrigation was evaluated. The MLs were constructed using PVC tubes, with dimensions of 100 mm inner diameter, 150 mm depth and 2.5 mm wall thickness. Four MLs were uniformly distributed on the soil surface of two weighing lysimeters conducted under bare soil, previously installed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 14 publications
(40 reference statements)
1
31
0
1
Order By: Relevance
“…The same was stated by Dalmago et al (2010) and Flumignam et al (2012). The Ke values had high comparison coefficients when ripening growth stage data were not included in the analysis.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The same was stated by Dalmago et al (2010) and Flumignam et al (2012). The Ke values had high comparison coefficients when ripening growth stage data were not included in the analysis.…”
Section: Discussionsupporting
confidence: 58%
“…The microlysimeter is PVC pipe filled up with soil, installed between crop rows and weighted periodically to calculate the mass difference by evaporation during the period desired. Flumignam et al (2012) compared the water evaporation from the soil lysimeters and microlysimeters, and concluded that the use of microlysimeters is valid. Dalmago et al (2010) validated the use of microlysimeters for absolute measurements and relative values of water evaporation from the soil to compare the planting methods.…”
Section: Introductionmentioning
confidence: 99%
“…Four microlysimeters with diameter of 150 mm and height of 200 mm were used in the determination of soil evaporation and later determination of daily soil evaporation coefficient (k e ), according to the methodology proposed and adapted by Flumignam et al (2012). Soil evaporation (E ML ) was determined according to Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Yunusa et al (1994) used a 1.1-metre-deep weighing lysimeter with a 2.27 m 2 cross-section to validate the Ritchie (1972) and Boesten and Stroosnijder (1986) E s models. Flumignan et al (2012) showed that there was close agreement between E s determined using micro-lysimeters and 1.3-metre-deep weighing lysimeters, respectively.…”
mentioning
confidence: 67%